Overlooked, dismissed, and downplayed: reversion of Mycobacterium tuberculosis immunoreactivity - Katie D. Dale; Alvaro Schwalb; Anna K. Coussens; Katherine B. Gibney; Alison J. Abboud; Krista Watts; Justin T. Denholm (European Respiratory Review, 2024)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis (Mtb). Following infection, immune responses to Mtb antigens can be measured using the tuberculin skin test or an interferon-γ release assay. The gain of Mtb immunoreactivity, a change from a negative to a positive tuberculin skin test or interferon-γ release assay result, is called conversion and has long been used as a measure of Mtb exposure. However, the loss of immunoreactivity (reversion; a positive followed by a negative result) has often been overlooked. Instead, in clinical and epidemiological circles, Mtb immunoreactivity is commonly considered to persist lifelong and confer a lifetime of disease risk. We present a critical review, describing the evidence for reversion from cohort studies, ecological studies and studies of TB progression risk. We outline the inconsistent reasons why reversion has been dismissed from common understanding and present evidence demonstrating that, just as conversion predominantly indicates prior exposure to Mtb antigens, so its opposite, reversion, suggests the reduction or absence of exposure (endogenous or exogenous). Mtb immunoreactivity is dynamic in both individuals and populations and this is why it is useful for stratifying short-term TB progression risk. The neglect of reversion has shaped TB research and policy at all levels, influencing clinical management and skewing Mtb infection risk estimation and transmission modelling, leading to an underestimation of the contribution of re-exposure to the burden of TB, a serious oversight for an infectious disease. More than a century after it was first demonstrated, it is time to incorporate reversion into our understanding of the natural history of TB.